Late-Holocene Indian summer monsoon variability revealed from a 3300-year-long lake sediment record from Nir'pa Co, southeastern Tibet. (April 2017) - Bird, Broxton W; Lei, Yanbin; Perello, Melanie; Polissar, Pratigya J; Yao, Tandong; Finney, Bruce; Bain, Daniel; Pompeani, David; Thompson, Lonnie G
Sedimentological and geochemical results from Nir'pa Co, an alpine lake on the southeastern Tibetan Plateau, detail late-Holocene Indian summer monsoon (ISM) hydroclimate during the last 3300 years. Constrained by modern calibration, elevated silt and lithics and low sand and clay between 3.3 and 2.4 ka and 1.3 ka and the present indicate two pluvial phases with lake levels near their current overflow elevation. Between 2.4 and 1.3 ka, a sharp increase in sand and corresponding decrease in lithics and silt suggest drier conditions and lower lake levels at Nir'pa Co. Hydroclimate expressions in the sedimentological proxies during the Medieval Climate Anomaly (MCA) and 'Little Ice Age' (LIA) are not statistically significant, suggesting that these events were minor compared to the millennial scale variability on which they were superimposed. However, decreasing sand and increasing lithics and silt during the MCA between 950 and 800 cal. yr BP may suggest briefly wetter conditions, while increasing sand and reduced lithics and silt from 500 to 200 cal. yr BP suggest potentially drier conditions during the LIA. Similarities with regional records from lake sediment and ice cores and speleothem records from the central and eastern Tibetan Plateau, India, and the Arabian Sea, suggest generally coherent late-Holocene ISM variability in these regions. Increased late-Holocene ISM intensity occurred during times when Tibetan Plateau surface air temperatures were warmer, Indo-Pacific sea surface temperatures were elevated, and the tropical Pacific was in a La Niña–like mean state. Conversely, aridity between 2.4 and 1.3 ka occurred in concert with cooling on the Tibetan Plateau and in the Indo-Pacific with more El Niño–like conditions in the tropical Pacific. Differences with western Tibetan records may reflect a weakened ISM and stronger westerlies in this region during the late-Holocene.